OPTIMIZATION THROUGH LINEAR PROGRAMMING METHOD SIMPLEX IN UMKM DONGKAL AWUG KANG CAKE IN BOGOR REGENCY - Antonius Cahyono; Prihono Prihono; Yunia Dwie Nurcahyanie (Sean Institute, 2023)
This study intends to explain the profit optimization model for UMKM to find out the profit optimization model for UMKM Kue Dongkal Awug Akang by using the simplex linear programming method. The population in this study was obtained from data from the results of the economic census, there were 142 business actors in the culinary field of food and beverages 508 MSMEs This research uses a single sampling technique namely the method of taking one MSME representing a number of the population More specifically, the sample chosen in this research is the UMKM Dongkal Awug Kang Cake The results of the study concluded that profit optimization can be applied to UMKM Dongkal Awug Kang Cakes which in actual conditions produce 24 portions of Traditional Dongkal Cakes (x1) and 37 portions of Contemporary Dongkal Cakes (x2) Then after optimization, it was found that there was an increase in production of 7 portions at optimal conditions. As well as the results of trimming waste on production factors efficiently so that it can increase optimal profit results.